2009
DOI: 10.1021/es900186e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Idle Reduction Technologies on Real World Fuel Use and Exhaust Emissions of Idling Long-Haul Trucks

Abstract: Idling long-haul freight tucks may consume nearly one billion gallons of diesel fuel per year in the U.S. There is a need for real-world data by which to quantify avoided fuel use and emissions attributable to idle reduction techniques of auxiliary power units (APUs) and shore-power (SP). Field data were obtained from 20 APU-equipped and SP-compatible trucks observed during 2.8 million miles of travel in 42 states. Base engine fuel use and emission rates varied depending on ambient temperature. APU and SP ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous research has suggested that non-fuel substitution strategies such as land use strategies to reduce VMT (Baum-Snow, 2010; Frank & Pivo, 1995;Boarnet, 2010), and behavioral strategies to avoid idling (Frey et al, 2009b;Gaines et al, 2012), reduce driving, and encourage transit use, have direct, if modest, impacts on human health (Dannenberg et al, 2003), energy use and CO 2 emissions (Makido et al, 2012;Norman et al, 2006). These strategies require significant multi-institutional efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that non-fuel substitution strategies such as land use strategies to reduce VMT (Baum-Snow, 2010; Frank & Pivo, 1995;Boarnet, 2010), and behavioral strategies to avoid idling (Frey et al, 2009b;Gaines et al, 2012), reduce driving, and encourage transit use, have direct, if modest, impacts on human health (Dannenberg et al, 2003), energy use and CO 2 emissions (Makido et al, 2012;Norman et al, 2006). These strategies require significant multi-institutional efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the alternative fuels strategy, the Clean Cities program aims to reduce petroleum consumption through idle reduction, VMT reduction, and other fuel-saving practices (United States Department of Energy, Energy Efficiency & Renewable Energy, 2016d). Idling wastes fuel and is associated with local pollutant emissions (Frey et al, 2009b). According to Argonne National Laboratory, idling can waste up to 0.5 gal of fuel per hour for passenger vehicles resulting in criteria pollutant and GHG emissions (Gaines et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…19/27 correlation between the number of idling stops and the daily working hours was observed (Person's correlation coefficient between the two variables is 0.52). Idling stop durations ranged from 5 s (equal to the threshold value set for the analysis of the idling stops) up to 2329 s, this number is much lower than that of trucks, where most of the idling is caused by idling stops longer than 1 hour (Frey, Kuo, & Villa, 2009). Short idling stops were much more frequent than long idling stops; indeed, the 50 % of the idling stops were shorter than 25 s, while the 10% of the idling stops were longer than 295 s (Fig.…”
Section: Idling With the Can-bus Data-loggermentioning
confidence: 99%
“…EPA categorizes the ability of construction contractors to affect activities associated with GHG emissions into three groups namely "most influence", "some influence possible", and "little influence", and lists equipment idling in the first category (EPA 2009). In addition to nonroad construction vehicles, idling is equally important for on-road long-haul truck activities because drivers have to take mandatory rest stops to meet the Federal Hours of Service (HOS) regulations (Frey et al 2009). Using simplifying assumptions, EPA estimates that 960 million gallons of diesel fuel are annually consumed as a result of long-haul truck idling (Lim 2002).…”
Section: Introductionmentioning
confidence: 99%